2022
DOI: 10.1093/braincomms/fcac257
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal association of sleep and Alzheimer biomarkers in cognitively unimpaired adults

Abstract: Sleep abnormalities are prevalent in Alzheimer’s disease, with sleep quality already impaired at its preclinical stage. Epidemiological and experimental data point to sleep abnormalities contributing to the risk of Alzheimer’s disease. However, previous studies are limited by either a lack of Alzheimer’s disease biomarkers, reduced sample size or cross-sectional design. Understanding if, when, and how poor sleep contributes to Alzheimer’s disease progression is important so that therapies can be targeted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 75 publications
3
31
1
Order By: Relevance
“…34 Conversely, sleep deprivation or shorter sleep duration was associated with pathologic tau in the CSF. 10,27 Considering the results of the Cox regression analysis, our longitudinal data suggest that prolonged sleep duration may be a prognostic marker for faster disease progression and tau accumulation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…34 Conversely, sleep deprivation or shorter sleep duration was associated with pathologic tau in the CSF. 10,27 Considering the results of the Cox regression analysis, our longitudinal data suggest that prolonged sleep duration may be a prognostic marker for faster disease progression and tau accumulation.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with our results, previous studies have reported that patients with AD have longer sleep duration or total time in bed than the control group, 25,26 which is associated with poor cognition and functional impairment. 26 Most studies have focused on sleep duration as a risk factor for incident dementia or Alzheimer disease in a cognitively unimpaired adult population, but not in patients with AD, which reported heterogeneous results; short sleep duration, 27 long sleep duration, 28 or both 29,30 were associated with Alzheimer pathology or cognitive decline. We also demonstrated that longer sleep duration was associated with faster disease progression from normal cognition to MCI or from MCI to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Both cross-sectional and longitudinal analyses of the EPAD dataset found associations between self-reported measures of sleep and AD biomarkers. Sleep disturbance was associated with lower CSF Aβ concentrations at both baseline and longitudinal follow-up, poor sleep quality was associated with higher CSF tTau at baseline and short sleep duration was associated with higher CSF pTau and tTau ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional studies showed cerebrospinal fluid (CSF) total and phosphorilated tau, Aβ and α−synuclein kinetics to be associated with sleep impairment 16,17 . Moreover, both total sleep deprivation and targeted slow-wave-sleep disruption increased overnight CSF Aβ content 16,18,19 . There is also evidence of higher brain interstitial waste product clearance during sleep, maybe due to an increased glymphatic influx 20,21 .…”
Section: Introductionmentioning
confidence: 98%